Standards for psychosocial care in pediatric cancer: adapted proposal for Latin American and Caribbean countries - Viviana Trigoso; Liliana Vásquez; Soad Fuentes-Alabi; Claudia Pascual; Teresa Méndez; Essy Maradiegue; Mariela Villegas; Elisa Perina; Eugenia Ahumada; João de Bragança; Marcela Zubieta; María del Pilar Jiménez; et al. (Pan American Health Organization, 2023)
Objective. To highlight the objectives, achievements, challenges, and next steps for the World Health Organization's Global Initiative for Childhood Cancer (GICC) framework, a project designed to improve psychosocial care (PSC) in pediatric cancer centers across Latin America and the Caribbean (LAC). Methods. The project was launched in Peru, the first GICC focal country, in November 2020. The diagnosis phase included a survey and a semistructured interview with health professionals to assess PSC practices in institutions, and a needs assessment survey for caregivers. In the second phase, a strategic plan was developed to address the identified needs, including the adaptation of PSC standards, the establishment of multicenter working groups, the expansion of the proposal, and the development of materials. Results. The study found that PSC was not being adequately provided in accordance with international standards. Six adapted standards were proposed and validated, and more than 50 regional health professionals participated in online activities to support the project. The implementation process is currently ongoing, with the establishment of five multidisciplinary working groups, one regional committee, and the production of 16 technical outputs. Conclusion. This project represents a substantial step forward to improve PSC for pediatric patients with cancer and their families in LAC countries. The establishment of working groups and evidence-based interventions strengthen the proposal and its implementation. Development of health policies that include PSC according to standards is needed to achieve sustainable results in the quality of life of children with cancer and their families.